High-performance data architectures : how to maximize your business with a cloud-based database - McKendrick, Joe; Huang, Ed (O'Reilly Media, Inc., 2023)
By choosing the right database, you can maximize your business potential, improve performance, increase efficiency, and gain a competitive edge. This insightful report examines the benefits of using a simplified data architecture containing cloud-based HTAP (hybrid transactional and analytical processing) database capabilities. You'll learn how this data architecture can help data engineers and data decision makers focus on what matters most: growing your business. Authors Joe McKendrick and Ed Huang explain how cloud native infrastructure supports enterprise businesses and operations with a much more agile foundation. Just one layer up from the infrastructure, cloud-based databases are a crucial part of data management and analytics. Learn how distributed SQL databases containing HTAP capabilities provide more efficient and streamlined data processing to improve cost efficiency and expedite business operations and decision making.